Implementasi Kode Etik Profesi Pustakawan Guna Mewujudkan Integritas Pustakawan ?Sebagai Kekuatan Utama Dalam Meningkatkan Citra Perpustakaan Di Badan ?Perpustakaan Universitas 17 Agustus 1945 Surabaya - Digna Novalia Emiliano Mbete (IJAL (Indonesian Journal of Academic Librarianship), 2024)
The librarian's professional code of ethics is the capital of professional values ??and rules, which must be carried out by all librarians in the process of their work. The purpose of this research is to find out how the Implementation of the Librarian Professional Code of Ethics to Realize the Integrity of Librarians as the Main Strength in Improving the Image of the Library at the Library Board of the University of 17 August 1945 Surabaya, whether the librarian has implemented the librarian professional code of ethics properly in accordance with the rules that have been set. . The research method used is a qualitative approach. The focus of the research is the implementation of the code of ethics for the librarian profession by the librarian at the University Library on 17 August 1945, Surabaya. Determination of informants by purposive sampling amounted to 6 (six) people while for data collection techniques used were observation, interviews, and documentation. The data analysis technique used is through data reduction, data presentation, data storage, and verification. The results of the study can be concluded that the Librarian of the Library Board of the University of 17 August 1945, Surabaya, in carrying out his obligations to the Nation and State, the librarian has carried out his duties well. In establishing a relationship with the user, the librarian uses a communal approach method. In establishing relationships with professional organizations, namely by attending seminars, the relationship between librarians and outsiders has been going very well. The librarians of the University of 17 August 1945 also understand the code of ethics for librarians that is used as their basis for carrying out their duties and responsibilities in the library. The basic attitude of the librarian is that the librarian has served the users well and is responsible for the job descriptions of each librarian. The impact that is felt if a librarian does not apply the code of ethics properly and correctly is that the librarian will become arrogant and indifferent to the user. However, until now, no one has violated the librarian's code of ethics. So the librarians of the University of 17 August 1945 in Surabaya have implemented the librarian's code of ethics and realized the integrity of the librarian well.